An Investigation of the Kinetic Modeling and Ignition Delay Time of Methanol—Syngas Fuel - Chen, Yexin; Jiang, Yankun; Wen, Xin; Liu, Huimeng (Frontiers in Energy Research, 2022)
The recycling of exhaust heat in internal combustion engines to dissociate the methanol, followed by its blending with methanol to produce engine fuel, is promising for improving the efficiency of engines and reducing emissions. The kinetic model MEOHSYNGAS1.0 for the methanol–syngas fuel is proposed by reducing the detailed chemical kinetic model (Mech15.34). Shock tube experiments are conducted to measure the ignition delay time of methanol blended with dissociated methanol gas at different dissociated methanol ratios (0%, 30%, 50%, and 100%). The model is validated by the experimental data of the present work and with data from the literature. The effects of the equivalence ratio, pressure, and dissociated methanol ratio on the ignition delay time are investigated through reaction path analysis and sensitivity analysis. When the dissociated methanol ratio does not surpass 50%, the ignition delay time increases with the increase of the dissociated methanol ratio, which is more obvious in the low temperature range, but decreases with the increase of temperature.